The potential of coconut waste as green roof materials to improve stormwater runoff - Noor Suraya, Romali; Fatin Afiqah, Ardzu; Muhamad Nurfaizal, Suzany (IWA Publishing, 2023)
Urbanization is one of the leading causes of urban flooding as rapid development produces more impervious areas in cities. The application of green roofs is regarded as an effective technology to minimize the adverse effects of urban development. The stormwater management capacities of green roofs have been extensively acknowledged, and they can retain rainfall and detain runoff. Nevertheless, Malaysia has experienced few green roof applications, and only limited literature is available concerning such topics. Additionally, the incorporation of waste and recycled material in green roof designs must be considered to ensure such projects benefit the environment as well as the economy. Therefore, the construction of a green roof utilizing recycled waste materials was attempted. An extensive green roof was constructed using beach morning glory and creeping ox-eye plants as vegetation layers, along with coconut waste, i.e., coconut fiber and coconut shell, as the medium for the filter and drainage layer, respectively. According to the results, the use of recycled coconut waste materials in the green roof operations reduced the peak flow by as much as 86%, while the use of commercial materials led to a reduction of 67%.